2020
DOI: 10.1002/ptr.6865
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid exerts an antagonistic effect on nonalcoholic fatty liver disease by regulating the YAP1/TAZ‐PPARγ/PGC‐1α signaling pathway

Abstract: Rosmarinic acid (RA) is a water‐soluble phenolic compound extracted from Boraginaceae and Lamiaceae. This study was designed to investigate the role and mechanism of action of RA in improving nonalcoholic fatty liver disease (NAFLD). Male SD rats maintained on a high fat diet and L02 cells stimulated with oleic acid were treated with RA. Our results showed that RA significantly reduced total cholesterol, triglycerides, low‐density lipoprotein cholesterol, alanine aminotransferase, aspartate aminotransferase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…In particular, intraperitoneal injection of allantoin can alleviate HFD-induced obesity and hyperlipidemia, and those effects are abolished by efaroxan pretreatment [ 36 , 42 ], which provides evidence that the activation of the imidazoline I 1 -receptor is associated with allantoin-mediated maintenance of lipid homeostasis. Although rosmarinic acid (10–200 mg/kg) and allantoin (5 mg/kg) have been reported to possess beneficial effects in mice fed an HFD [ 36 , 43 , 44 , 45 ], the effective concentrations of rosmarinic acid and allantoin administered directly into animals in the aforementioned references appears too high to be reached in vivo by administration of 200 mg/kg M-LB/CS in the present study. In addition, HPLC chromatogram after eluting LBE and CSE indicated that there were many peaks beyond rosmarinic acid and allantoin, and several phytochemicals contained in two herbs (e.g., ursolic acid, oleanolic acid, caffeic acid, luteolin, rutin, maysin, and α-terpineol) also have potential to alleviate obesity [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussioncontrasting
confidence: 56%
“…In particular, intraperitoneal injection of allantoin can alleviate HFD-induced obesity and hyperlipidemia, and those effects are abolished by efaroxan pretreatment [ 36 , 42 ], which provides evidence that the activation of the imidazoline I 1 -receptor is associated with allantoin-mediated maintenance of lipid homeostasis. Although rosmarinic acid (10–200 mg/kg) and allantoin (5 mg/kg) have been reported to possess beneficial effects in mice fed an HFD [ 36 , 43 , 44 , 45 ], the effective concentrations of rosmarinic acid and allantoin administered directly into animals in the aforementioned references appears too high to be reached in vivo by administration of 200 mg/kg M-LB/CS in the present study. In addition, HPLC chromatogram after eluting LBE and CSE indicated that there were many peaks beyond rosmarinic acid and allantoin, and several phytochemicals contained in two herbs (e.g., ursolic acid, oleanolic acid, caffeic acid, luteolin, rutin, maysin, and α-terpineol) also have potential to alleviate obesity [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussioncontrasting
confidence: 56%
“…AMPK activation inhibits lipid accumulation and de novo lipid synthesis by inactivating acetyl-CoA carboxylase (ACC) and stimulates fatty acid oxidation by upregulating CPT1 [20,62]. A previous report showed that rosmarinic acid prevented NAFLD by maintaining mitochondrial integrity [63]. Vasileva et al [64] claimed that rosmarinic acid inhibited adipogenic genes and proteins in human adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In several reports, RA has acted as hepatoprotective agent through modulation of inflammatory cascades and oxidative imbalances (Luo et al 2021 ; Touiss et al 2021 ). RA has attenuated chromium-induced hepatorenal oxidative damage and the formation of preneoplastic lesions in rats through upregulation of the Nrf2 signaling pathway and antioxidant actions (Khalaf et al 2020 ).…”
Section: Pharmacological Properties Of Ramentioning
confidence: 99%